De-coding new regionalism : shifting socio-political contexts in Central Europe and Latin America - Scott, James Wesley, 1956- (Urban and regional planning and development., 2009)
Bringing together comparative case studies from Central Europe and South America, this book focuses on 'new' regions - regions created as political projects of modernization and 're-scaling'. Through this approach it de-codes 'New Regionalism' in terms of its contributions to institutional change, while acknowledging its contested nature and contradictions.